Multifunctional Asymmetric Bilayer Aerogels for Highly Efficient Electromagnetic Interference Shielding with Ultrahigh Electromagnetic Wave Absorption - Qi, Cheng‑Zhang; Min, Peng; Zhou, Xinfeng; Jin, Meng; Sun, Xia; Wu, Jianjun; Liu, Yanjun; Zhang, Hao‑Bin; Yu, Zhong‑Zhen (Nano-Micro Letters, 2025)
Although multifunctional electromagnetic interference (EMI) shielding materials with ultrahigh electromagnetic wave absorption are highly required to solve increasingly serious electromagnetic radiation and pollution and meet multi-scenario applications, EMI shielding materials usually cause a lot of reflection and have a single function. To realize the broadband absorption-dominated EMI shielding via absorption–reflection–reabsorption mechanisms and the interference cancelation effect, multifunctional asymmetric bilayer aerogels are designed by sequential printing of a MXene-graphene oxide (MG) layer with a MG emulsion ink and a conductive MXene layer with a MXene ink and subsequent freeze-drying for generating and solidifying numerous pores in the aerogels. The top MG layer of the asymmetric bilayer aerogel optimizes impedance matching and achieves re-absorption, while the bottom MXene layer enhances the reflection of the incident electromagnetic waves. As a result, the asymmetric bilayer aerogel achieves an average absorption coefficient of 0.95 in the X-band and shows the tunable absorption ability to electromagnetic wave in the ultrawide band from 8.2 to 40 GHz. Finite element simulations substantiate the effectiveness of the asymmetric bilayer aerogel for electromagnetic wave absorption. The multifunctional bilayer aerogels exhibit hydrophobicity, thermal insulation and Joule heating capacities and are efficient in solar-thermal/electric heating, infrared stealth, and clean-up of spilled oil. Highlights: 1 The multifunctional asymmetric bilayer MXene-graphene oxide (MG)-MXene aerogel with ultrahigh absorption electromagnetic interference (EMI) shielding is constructed by 3D printing and subsequent freeze-drying. 2 The asymmetric bilayer aerogel achieves ultrahigh electromagnetic wave absorption coefficient of 0.95, and maintains a high EMI shielding effectiveness of over 100 dB. 3 The multifunctional asymmetric aerogel with ultrahigh electromagnetic wave absorption, infrared camouflage, solar-thermal heating, and clean-up of organic solvents and spilled crude oil is developed for multi-scenario applications.